Evaluación de la captura de carbono de tres especies forrajeras en Zungarococha Iquitos-2019 - Del Castillo Villacorta, Miguel Angel (2022)
The Work of Investigation was developed in the Shop Garden Agrostologico, located in the Km. 5,800 of the highway Iquitos Zungarococha, Saint John the Baptist District, County of Maynas, Department of Loreto to some 60 minutes of the city of Iquitos, with the objective of evaluating the Capture of Carbon of the black grass, I pasture Brachiaria sp and of the king green gras evaluated to the 6ta week, The population was conformed by the plants in study that for bed of 10m2 c/u one had 40 plants that which made a total of 1,440 plants (36 beds), to complete the objectives outlined investigation work presently the Design of Complete Blocks you/he/she was used at random (DBCA), with four (4) treatments and three (3) repetitions, obtaining the following results; the capture of carbon of the grasses in study evaluated to the 6ta week, they have significant values being the T3 (King green grass) who occupies the first Order of Merit on the average with 66.0 g/m2, the T2 (Brachiaria sp) with an average of 34.0 g/m2 it occupies the second place, the T1 (I Pasture black) it occupies the third place respectively with 26.0 g/m2. The hypothesis outlined investigation work presently is accepted the grasses since in study they have significant effects with respect to the accumulation of carbon that you register during its vegetative developments.